Attitude towards research in health sciences and social sciences master's students - YACE MARTINEZ, Jessica Maryluz (2020)
Objective. Determine the level of attitude toward scientific research and towards statistics in students of the masters of health sciences and social sciences, as well as the identification of their academic background. Materials and methods. A quantitative, observational, analytical and applied study was carried out. Results It was found that 70.5% of students are female, 57.6% if they have children, 98.5% study and work currently, 41.7% come from other private universities than the one from origin, 58 , 3% graduated under the thesis modality, 86.4% only have a bachelor's degree, 17.4% have done some scientific publication and 10.6% have made a publication in an indexed journal, students who more research carried out are those of the master's degree in social sciences (university teaching), 59.8% of all students have a favorable attitude towards scientific research and 62.9% of all students have a favorable attitude towards statistics , the students of the master's degree in social sciences (university teaching) presented better levels of favorable attitude toward scientific and statistical research compared to the master's degree in health sciences (health management) Conclusions: Master's students of health sciences and social sciences present a favorable attitude towards scientific research and towards statistics.Keywords: attitude, research, students, statistics.